Beyond Profession: The Impact of the Job on Probation Personnel - Münevver Eryalçın; Talip Eryalçın (Social Sciences)
This study aims to assess the impact of work on managers, specialists, and probation officers in Türkiye. The research seeks to enhance understanding of how work life affects personnel and to propose policy recommendations from a social work perspective to improve professional well-being. A qualitative research design utilizing a phenomenological approach was adopted. Data collection involved an individual information form and a semi-structured in-depth interview form, developed by the researchers, to evaluate work-related impacts. Through purposive quota sampling, 30 participants, including specialists, managers, and probation officers, were recruited from probation offices with the highest workload across Türkiye’s seven regions. The data were descriptively analyzed using the Maxqda 2020 software. The findings reveal that professional, individual, and institutional stress factors significantly impact the well-being of probation personnel. While staff report deriving satisfaction from helping individuals break the cycle of crime and receiving positive feedback, they encounter challenges such as emotional labor, lack of professional recognition, and inadequate working conditions. Security concerns related to working with probationers were also emphasized. During the pandemic, disruptions in rehabilitation programs, increased recidivism, and perceptions of impunity were noted. The study underscores the necessity for improved working conditions, benefits, and professional respect to enhance the welfare of probation personnel.